Green Marketing, Awareness, Media Exposure, and Accessibility: Drivers of Green Consumption Among Indonesian Gen Z - Esterina, Hellend; Yaniarta, Vanesa; Lindawati, Ang Swat Lin (Journal of Environmental Accounting and Management, 2026)
Indonesia faces significant environmental challenges, particularly evident in the disparity between expressed green consumption intentions and actual behaviors. Gen Z, known for their environmental awareness, is a key demographic to consider in addressing this gap. This study aims to comprehend the factors influencing green consumption behavior among Indonesian Gen Z. By examining the relationships between Green Marketing, Green Awareness, Media Exposure, and Green Product Accessibility towards Green Consumption, the research identify the key drivers for promoting sustainable consumption practices. A partial least squares-structural equation modelling (PLS-SEM) was employed to analyze the 388 data collected through survey distributed to Indonesian Gen Z. The finding of this research reveals that Green Marketing has the most significant influence on Green Consumption among Indonesian Gen Z, followed by Media Exposure and Green Awareness. Green Product Accessibility, despite its influence, exhibits the least significant impact on green consumption behavior within this demographic. Reliability measures confirm validity for all constructs. These findings support the Theory of Planned Behavior (TPB) and highlight Green Marketing as a critical driver of sustainable consumption, offering insights for achieving the SDGs 2030.